Effectiveness Of Animation-Based Psychoeducation On Adolescent Mental Health And Risk Behavior: A Quasi-Experimental Study - Sinaga, Rosmani; Pangaribuan, Ingka Kristina; Sembiring, Isyos Sari; Simbolon, Marlina Lasmawati; Manurung, Indra Septiady; Hia, Lidia Widarni; Gulo, Fransiska (Journal of Applied Nursing and Health, 2026)
Background: Adolescent mental health and risky behaviors, including the KRR TRIAD (Risky Sexual Behavior, Drug Abuse, and HIV/AIDS), remain significant public health challenges in Indonesia that contribute to school dropout rates. This study aimed to evaluate the effectiveness of PENA (Education and Animation)-based psychoeducation in improving knowledge and behavior related to mental health, TRIAD KRR, and dropout prevention. Methods: This quasi-experimental study with a pretest-posttest control group followed the TREND (Transparent Reporting of Evaluations with Nonrandomized Designs) reporting guideline. A sample of 124 students was selected using a simple random sampling technique. The intervention group received PENA-based psychoeducation for a duration of 4 weeks (two sessions per week), while the control group received leaflets. Data were collected using a questionnaire that had been tested for validity and reliability. Data were analyzed using the Mann-Whitney test. Results: The intervention group showed a significant increase in knowledge (Median 80, IQR: 75–85) compared to the control group (Median 45, IQR: 40–50) with $p = 0.015$. Furthermore, the intervention group demonstrated better behavior in preventing TRIAD KRR and school dropout with p < 0.001. Conclusion: PENA-based psychoeducation is more effective than traditional leaflets in improving knowledge and fostering positive behavioral changes among adolescents.